Desempenho agronômico, heterose e estabilidade fenotípica de genótipos de cebola em Guarapuava - PR - Quartiero, Anderson (2012)
The objective of this study was to evaluate the performance of 50 genotypes of onion (a lineage and eight hybrid experimental group Baia, 10 lineages and 22 experimental hybrids group Creole, six open pollinated varieties and three hybrids) in three cropping epochs in Guarapuava-PR, in 2010. Three experiments were conducted in a randomized block design with three replications. Seedlings at 45 days of age were transplanted on May 27, June 30 and August 3, corresponding to three epochs. Were evaluated for agronomic characteristics and post-harvest of bulbs. For the stability of genotypes phenotypic analysis was performed by the method of Annicchiarico. Heterosis was estimated seven hybrids. There was a significant effect of genotype x epochs for all traits. The first epoch yielded the highest average percentage of bulbs with higher commercial value (classes 3 + 3 + 4 full), higher concentration of mass media and increased productivity of bulbs. The third epoch got the lowest grades. For bulb yield, only 26% of genotypes showed overall confidence index (wi) above 100%. The experimental hybrids HB1266, HB2285, HC3119, HC3126, HC3479 and HC3488 showed the highest levels of trust for productivity and for the percentage of bulbs classes with higher commercial value (3 + 3 + 4 full), although the first epoch has not participated in most productive group of genotypes. The average heterosis observed for the average mass of bulbs was 38%, ranging from 16% (HC3485) to 63% (hybrid HC3483) and productivity was 36%, ranging from 16% (HC3485) to 57% (HC3483). The average heterosis for the content of pyruvic acid in the bulbs was negative (-13.36%). For the soluble solids average heterosis was 9.43% and the hybrid HC3477 showed the highest (18.14% = 1.43 º Brix).